Formation of future managers for team building activities - I V Khlyzova (Peoples' Friendship University of Russia (RUDN University), 2009)
The future managers' formation model for team building is described in this article such as model type, structure, and functions, terms and factors of the efficient implementation. The approbation results were produced and analyzed.